MARICULTURE DEVELOPMENT IN INDONESIA: Prospects and Constraints - Michael A. Rimmer (Indonesian Aquaculture Journal, 2010)
Mariculture is an important component of Indonesian fisheries and aquaculture production, directly contributing an estimated US$ 320 million in 2008. Because most mariculture production is focussed on producing for export markets, mariculture production is an important source of foreign earnings for the Indonesian economy. This paper reviews the current status and prospects for continuing development of mariculture in Indonesia. Currently the major mariculture commodity in Indonesia is seaweed for carrageenan production. Seaweed production accounts for 98% of total Indonesian mariculture production and 84% of value. The other major commodity groups are marine finfish and pearl oysters. Commodities being developed for mariculture in Indonesia include abalone and spiny lobsters. Prospects for continued development of mariculture in Indonesia appear positive. Indonesia has several advantages for mariculture development, including many potential mariculture sites, a stable tropical climate, and does not suffer from cyclonic storms. The Government of Indonesia is planning to increase aquaculture production substantially over the next four years, including mariculture production. Globally, demand for seafood products is expanding due to increasing population and increased per capita consumption of fish products. Constraints to the continued development of mariculture in Indonesia include: limited seed supply, particularly of species which cannot be economically produced in hatcheries, such as spiny lobsters; need to develop more efficient production systems for some marine finfish; the need to improve environmental sustainability by improving feeds and reducing environmental impacts; and market issues relating to environmental sustainability.